2021
DOI: 10.14201/rlop.23681
|View full text |Cite
|
Sign up to set email alerts
|

Media Choice and the Polarization of Public Opinion About Covid-19 in Brazil

Abstract: Brazil is one of the countries most affected by the Covid-19 pandemic. Yet, while rates of contagion and deaths increase over time, polls show that opinions about the pandemic become less concerned about the virus and less supportive of mitigation measures. According to observers, a key factor in this process is President Bolsonaro’s denialist stance. In this paper, we show that patterns of media choice help explain how Bolsonaro influences public opinion over time. Using three online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
11
0
4
Order By: Relevance
“…[29] On the other hand, similar studies from Malaysia, [30] India, [31] Lebanon, [32] and China [33] have found somewhat lower knowledge levels about COVID-19, but not as low as that observed in a study conducted in Bangladesh, which showed that only 33% of the participants had a good level of knowledge about COVID-19. [34] The fact that during this study's data collection period, Brazil had one of the fastest-growing COVID-19 epidemics in the world, [2] which resulted in it being the country with most cases and deaths in Latin America, [35] and the intense coverage of the pandemic by Brazilian mainstream media, with high-quality content due to the participation of well-known researchers and health professionals, [36] might explain the high level of knowledge found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…[29] On the other hand, similar studies from Malaysia, [30] India, [31] Lebanon, [32] and China [33] have found somewhat lower knowledge levels about COVID-19, but not as low as that observed in a study conducted in Bangladesh, which showed that only 33% of the participants had a good level of knowledge about COVID-19. [34] The fact that during this study's data collection period, Brazil had one of the fastest-growing COVID-19 epidemics in the world, [2] which resulted in it being the country with most cases and deaths in Latin America, [35] and the intense coverage of the pandemic by Brazilian mainstream media, with high-quality content due to the participation of well-known researchers and health professionals, [36] might explain the high level of knowledge found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Las preferencias políticas han sido identificadas como un factor que también explica la opinión de los ciudadanos respecto a creencias sobre temas científicos (Kahan et al, 2012;McCright y Dunlap, 2011;Rutjens et al, 2018). En línea con esta literatura, diversos estudios han encontrado que las preferencias políticas inciden en la percepción de gravedad de COVID-19 (Aruguete et al, 2021;Aruguete y Calvo, 2020;Barrios y Hochberg, 2021;Batista Pereira y Nunes, 2021;Clinton et al, 2021;Pennycook et al, 2022;Pickup et al, 2020). Específicamente en países con presidentes que menospreciaron la gravedad de la enfermedad por coronavirus, se observa que los ciudadanos tienden a preocuparse menos por la pandemia.…”
Section: Revisión Teóricaunclassified
“…Diversos estudios encuentran que la percepción de gravedad del virus está asociada a las preferencias políticas (Aruguete et al, 2021;Aruguete y Calvo, 2020;Barrios y Hochberg, 2021;Batista Pereira y Nunes, 2021;Clinton et al, 2021;Pennycook et al, 2022;Pickup et al, 2020) La ideología e identificación partidista fungen como filtros por los que los ciudadanos forman opiniones sobre asuntos públicos. Por esto, los mensajes de la élite influyen en la percepción de los ciudadanos sobre diferentes temas (Zaller, 1992).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Public opinion research suggests that citizen perceptions of the coronavirus (COVID-19) pandemic are influenced by partisan affiliation. Partisanship shapes an individual's perception of their risk of falling victim to COVID-19, their assessment of the overall gravity of the pandemic, and attitudes toward mitigation measures (Aruguete and Calvo, 2020;Dryhurst et al, 2020;Clements, 2020;Pickup et al, 2020;Sobral et al, 2020;Batista Pereira and Nunes, 2021;Calvo and Ventura, 2021;Clinton et al, 2021;Gadarian et al, 2021;Arugete et al, 2021). The preponderance of research on how partisan affiliation shapes COVID-19 risk perception was carried out in the global North, primarily in the United States (US).…”
Section: Introductionmentioning
confidence: 99%